Hubungan Antara Kepuasan Pasien Terhadap Pelayanan Kesehatan di Wilayah Kerja Puskesmas Oekabiti dalam Kondisi Pandemi Covid-19 - Sri Hartanti Masneno; Muntasir, Muntasir; Tadeus A. L. Regaletha (Yayasan Literasi Sains Indonesia, 2022)
Patient satisfaction is a feeling that arises after someone receives a service and assesses the service he receives as expected or not. So that service providers play an important role in being able to meet the needs of every customer. Patient satisfaction is determined by 5 dimensions of service quality, reliability, tangibles, responsiveness, assurance, and empathy. The percentage of NTT residents who experienced illness but did not seek treatment for the past month claiming the main reason for not seeking outpatient in 2020, people chose to self-medicate as much as 72,81% compared to other reasons, namely waiting time for services as much 1,38%, feel no need as much as 23,16%, no transportation costs as much as 1,54%, and no medication costs as much as 1,10%. Oekabiti health center in 2021- January 2022 there is an increase and decrease in the number of outpatient visits. This study aims to determine the relationship between patient satisfaction with health services in the working area of the Oekabiti Health Center in the Covid-19 pandemic. This type of research is an analytical survey, with a design Cross Sectional Research the number of samples is 339 visitors to the Oekabiti Health Center. Selected by accidental sampling method which was researched and tested using the Chi-square test to determine the relationship with the variable of patient satisfaction with health services at the Oekabiti Health Center. The results of the research at the Oekabiti Health Center showed that there was a relationship between reliability, tangibles, responsiveness, assurance, and empathy with patient statisfaction based on the results of the Chi-square test. Wait for the uncomfortable medication to be received.